HABILIDADES COGNITIVAS EN LA EDUCACIÓN - Mancilla Castro, César Augusto
The purpose of this article was to analyze the importance related to cognitive skills based on three different perspectives such as instructor (teacher), apprentice (student) and administrative staff and the way these abilities have been developed.The process was carried out through a survey, where 7 questions focused on the development of cognitive skills were analyzed. This survey was shared with the three areas mentioned above. It was possible to show that of the 3 perspectives; there was a great participation by apprentices or students, where most of those investigated have heard about this type of skills; and in the same way, it was possible to determine that the most representative skills to function in the world of work are: orientation, language and social cognition. A significant question was raised that analyzed: in the resolution of a conflict, of the following options, which do you consider to be the skills that should be applied? resulting in that of 66 people surveyed; 53 said reasoning, and 49 people expressed understanding. As it was a question where they could choose several options, the answers were very varied.